Chaos‐based fast colour image encryption scheme with true random number keys from environmental noise. Issue 5 (23rd March 2017) - Liu, Hongjun; Kadir, Abdurahman; Sun, Xiaobo
Abstract : The paper proposes a chaos‐based colour image encryption scheme, the highlight is that the randomly sampled noise signal is applied to serve as the initial values of a chaotic system. The 256‐bit hash value of noise is transformed into the one‐time initial values of the Liu system. The sequences generated by Liu system are subjected to three batteries of TestU01. Exclusive OR, the only operation, is applied to diffuse the pixels, and some measures are taken to speed up the encryption process. Finally, some statistical tests are performed to assess reliability and efficiency of the proposed cryptosystem in terms of time complexity and security.